CO2 capture by antisublimation process and its technical economic analysis. Issue 1 (3rd January 2013) - Pan, Xueqin; Clodic, Denis; Toubassy, Joseph
Abstract CO2 capture by antisublimation consists in cooling the flue gases down to the freezing temperature of CO2 and frosting CO2 on a low temperature heat exchanger surface at a temperature range defined by the CO2 concentration in the flue gases and the CO2 capture efficiency. CO2 is then defrosted and recovered in a liquid state. This CO2 capture process by antisublimation is called AnSU®. The CO2 frosting temperature in flue gases is much lower than the triple point of water and therefore before CO2 capture, water contained in flue gases is removed to reach high purity CO2. This paper presents an overview of the antisublimation process and a brief review of test benches that have been set up in laboratory and on industry sites for validation and optimization of the antisublimation process dating back to the first one constructed in 2003. Energy consumption and cost penalty of CO2 capture by antisublimation are evaluated for a coal‐fired power plant. A technical and economic analysis has been made and compared to CO2 capture by oxycombustion for a cement plant. Those two processes can be seen as cryogenics options and the detailed comparison gives insight into where energy losses take place and which capture process could be most adapted depending on specifications of the cement industry. © 2012 Society of Chemical Industry and John Wiley & Sons, Ltd